Respuesta :

Good evening ,

Answer:

Un = -16n +42

Step-by-step explanation:

Un = U1 + (n-1)r

U1 = 26

r = 10-26 = -16

Un = U1 + (n-1)r

     = 26 + (n-1)(-16)

     = 26 - 16n + 16

     = -16n +42.

:)

Answer:

[tex]a_{n}[/tex] = 42 - 16n

Step-by-step explanation:

Note there is a common difference d between consecutive terms

d = 10 - 26 = - 6 - 10 = - 22 - ( - 6)) = - 16

This indicates that the sequence is arithmetic with n th term ( explicit formula )

[tex]a_{n}[/tex] = a₁ + (n - 1)d

where a₁ is the first term and d the common difference

Here a₁ = 26 and d = - 16, thus

[tex]a_{n}[/tex] = 26 - 16(n - 1) = 26 - 16n + 16 = 42 - 16n

ACCESS MORE
EDU ACCESS
Universidad de Mexico